Psychological Determinants of Investment Decisions: Analyzing Financial Behavior in Personal Investments - Chandra Bhooshan Singh; Nistha Sharma; Mariyam Ahmed (PT Agung Media Publisher, 2024)
Understanding the psychological factors that influence investor behavior is critical in the dynamic world of financial markets. Financial conduct encompasses the decisions and behaviors individuals exhibit in managing their finances, including investments in various asset classes. Factors such as risk tolerance, cognitive biases, emotional influences, and financial knowledge significantly shape investment outcomes. Gaining long-term financial success requires mastery over these behavioral aspects. This study investigates the influence of three psychological factors—information asymmetry, problem framing, and risk propensity—on the investment decisions of 220 active investors trading on the National Stock Exchange (NSE) and Bombay Stock Exchange (BSE). A quantitative research approach was employed, utilizing a structured questionnaire to collect data. Statistical analyses, including regression and correlation analysis, were used to assess the relationships between these psychological variables and investment behaviors. The results reveal significant correlations between psychological factors and investment decisions. Information asymmetry, problem framing, and risk propensity were found to strongly influence individual investor choices. These findings shed light on the intricate role that cognitive biases and psychological processes play in shaping financial decision-making. The study's findings offer valuable insights into the psychological drivers behind investment behavior. By highlighting the impact of these factors, the research contributes to both academic understanding and practical applications for financial professionals. The results underscore the importance of enhancing financial literacy and investor education, enabling more informed decision-making and promoting improved financial outcomes.